(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this article, harmonic oscillations of a mathematical and spring pendulum are considered, and graphs of the dependence of speed and acceleration on time and coordinates were obtained using the Microsoft Excel software tool.